Implementation of School Quality Management in Indonesia - Yulia Ainur Rofiqoh; Istikomah Istikomah; Hidayatulloh Hidayatulloh (Proceedings of The ICECRS, 2020)
Every educational institution which is engaged in services and society, must be entitled to the goals in accordance with the institutions that can achieve progress and success of other educational institutions. Therefore educational institutions must be able to create schools that are innovative, innovative and of high quality. This is done competing with other educational institutions, and creating quality schools. This research tries to. Through this research, it is expected to be a reference for schools. "Because school is a place for human resources to become superior human beings in the future and in the future. Quality in education in the form of services which require help and expectations of parties related to students. The type of research used in research is library research or research libraries. What is discussed with library research (Library Research) At this stage, researchers conduct what is called literature study, namely reference book research.